Polarization and anisotropic emission of K-shell radiation from heavy few electron ions - Thorn, D. B.; Gumberidze, A.; Trotsenko, S.; Banaś, D.; Beyer, H.; Bostock, C.J.; Bray, I.; Chen, W.; DuBois, R.; Fontes, C.J.; Fritzsche, S.; Fursa, D.V.; et al. (Canadian journal of physics, 2011)
The population of magnetic sublevels in hydrogen-like uranium ions has been investigated in relativistic ion-atom collisions by observing the subsequent X-ray emission. Using the gas target at the experimental storage ring facility we observed the angular emission of Lyman-α radiation from hydrogen-like uranium ions. The alignment parameter for three different interaction energies was measured and found to agree well with theory. In addition, the use of different gas targets allowed for the electron-impact excitation process to be observed.